1989
DOI: 10.1159/000266810
|View full text |Cite
|
Sign up to set email alerts
|

A Study of the Mechanisms of Chloroquine Retinopathy

Abstract: The influence of chloroquine on lipid peroxidation in rat and rabbit retinas has been studied. Chloroquine retinopathy is not followed by an increase in lipid peroxidation, and the antioxidant ionol does not prevent the drug effect. Chloroquine has an inhibitory action on induced lipid peroxidation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0
1

Year Published

1993
1993
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 7 publications
(9 reference statements)
0
1
0
1
Order By: Relevance
“…Disturbances in structural inteCorrespondence to: T. Maertins grity of the retina, such as degenerative changes, also lead inevitably to measurable functional changes. Morphological changes in the rat retina occur genetically (Dowling and Sidman 1962;Ruchoux et al 1990) or may be induced by light (Noell et al 1966) or various chemicals and drugs such as organometallic compounds (Chang and Dyer 1983), lead (Fox and Chu 1988), organophosphates (Imai et al 1983), oxygen (Penn and Thum 1989), urethane (Korte et al 1984), GABA (Butler et al 1987), amoscanate (Schaeppi et al 1987), glutamate (Gilad and Gilad 1989), lithium (Federspiel-Eisenring et al 1988), and chloroquine (Ivanina et al 1989). In the study of Imai et al (1983) substance-induced degenerative changes in the rat retina were subjected to a comparative evaluation on the basis of the three examination methods mentioned above; it was demonstrated that ERG changes appeared before any structural damage could be detected.…”
Section: Introductionmentioning
confidence: 99%
“…Disturbances in structural inteCorrespondence to: T. Maertins grity of the retina, such as degenerative changes, also lead inevitably to measurable functional changes. Morphological changes in the rat retina occur genetically (Dowling and Sidman 1962;Ruchoux et al 1990) or may be induced by light (Noell et al 1966) or various chemicals and drugs such as organometallic compounds (Chang and Dyer 1983), lead (Fox and Chu 1988), organophosphates (Imai et al 1983), oxygen (Penn and Thum 1989), urethane (Korte et al 1984), GABA (Butler et al 1987), amoscanate (Schaeppi et al 1987), glutamate (Gilad and Gilad 1989), lithium (Federspiel-Eisenring et al 1988), and chloroquine (Ivanina et al 1989). In the study of Imai et al (1983) substance-induced degenerative changes in the rat retina were subjected to a comparative evaluation on the basis of the three examination methods mentioned above; it was demonstrated that ERG changes appeared before any structural damage could be detected.…”
Section: Introductionmentioning
confidence: 99%
“…Під час палінологічного дослідження міоспор палеозою Волино-Поділля використано праці [1, 2, 11-18, 20, 22-26 Стра тигра фі чн е та г е огра фі чн е п ошир ен ня . Нижній карбон європейської частини Росії (палінозони Е-А) [1,21]; о. Шпіцберген [23,30,31]; Прип'ятської западини [13]; візе (нижньовізейський під'ярус, куличківськанижня частина олеськівської світ, палінозони С-І) ВПО СЄП [5,6].…”
unclassified